Perbandingan Latihan Push Up dan Beban Dumbell Terhadap Kecepatan Pukulan Straight pada Atlit Tinju Amatir Sasana Lipang Bajeng Kabupaten Takalar - Latuheru, Melerand Evert; Lolangluan, Welem Arawaman; Wattimury, Hermanus (MANGGUREBE: Journal Physical Education, Health and Recreation, 2021)
This study aims to find out about the comparison of push up training and dumbbell weights to the speed of a straight punch in amateur boxing athletes. This type of quantitative research is an experimental form using a cross sectional study approach. The population is all 30 boxing amateur boxing athletes. The sampling technique is by sampling saturation. The population was used as a sample of Research Instruments divided into 2 groups of 15 people. The technique of group division technique uses the Randomized group method, while using the T-test. The results showed that there was no comparison as well as a significant difference between push-up training with dumbbell load to 0.454 straight stroke speed, seen from the t-count of push-up and dumbbell load -0,770